Matematyka

Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko

Wydawnictwo:Nowa Era

Rok wydania:2014

Oblicz 4.33 gwiazdek na podstawie 9 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

Przypomnijmy prawa działań na potęgach:

 

`a)` 

`((3/5)^5:(7/5)^3)*(3/7)^-4=(3/5)^5*(5/7)^3*(3/7)^-4=3^5/5^5*5^3/7^3*(7/3)^4=` 

`=3^5/5^5*5^3/7^3*7^4/3^4=3^(5-4)*5^(3-5)*7^(4-3)=3*5^-2*7=3*1/25*7=21/25` 

 

 

`b)` 

`((1 4/5)^3*(1 1/2)^-6):(5/8)^-2=((9/5)^3*(3/2)^-6):(8/5)^2=`   

`=((9/5)^3*(2/3)^6)*(5/8)^2=(9/5)^3*(2/3)^6*(5/8)^2=` 

`=9^3/5^3*2^6/3^6*5^2/8^2=(3^2)^3/5^3*2^6/3^6*5^2/(2^3)^2=` 

`=strike(3^6)/5^3*strike(2^6)/strike(3^6)*5^2/strike(2^6)=5^2/5^3=1/5` 

 

 

`c)` 

`(8/9)^4*(16/27)^-2=8^4/9^4*(27/16)^2=(2^3)^4/(3^2)^4*27^2/16^2=2^12/3^8*(3^3)^2/(2^4)^2=2^12/3^8*3^6/2^8=`  

`=2^(12-8)*3^(6-8)=2^4*3^-2=16*1/9=16/9` 

 

 

`d)` 

`(88/135)^-2:(45/44)^3=(88/135)^-2*(44/45)^3=((2^3*11)/(5*3^3))^-2*((2^2*11)/(5*3^2))^3=(2^-6*11^-2)/(5^-2*3^-6)*(2^6*11^3)/(5^3*3^6)=`  

`=(2^-6*11^-2*2^6*11^3)/(5^-2*3^-6*5^3*3^6)=11/5` 

 

 

`e)` 

`((4/9)^5*(1 1/2)^10)^17=(((2/3)^2)^5*(3/2)^10)^17=((2/3)^10*(3/2)^10)^17=((2/3*3/2)^10)^17=(1^10)^17=1^170=1` 

 

 

`f)` 

`(5/14)^-6*(56/15)^-6*(2/3)^12=(strike5^1/strike14^1*strike56^4/strike15^3)^-6*(2/3)^12=(4/3)^-6*(2/3)^12=` 

`=(4/3)^-6*(3/2)^-12=(4/3)^-6*((3/2)^2)^-6=(4/3)^-6*(9/4)^-6=` 

`=(strike4^1/strike3^1*strike9^3/strike4^1)^-6=3^-6=1/3^6=1/729`